Klebsiella pneumoniae survives within macrophages by avoiding delivery to lysosomes. (17th July 2015) - Cano, Victoria; March, Catalina; Insua, Jose Luis; Aguiló, Nacho; Llobet, Enrique; Moranta, David; Regueiro, Verónica; Brennan, Gerard P.; Millán‐Lou, Maria Isabel; Martín, Carlos; Garmendia, Junkal; Bengoechea, José A.
Summary K lebsiella pneumoniae is an important cause of community‐acquired and nosocomial pneumonia. Evidence indicates that Klebsiella might be able to persist intracellularly within a vacuolar compartment. This study was designed to investigate the interaction between Klebsiella and macrophages. Engulfment of K. pneumoniae was dependent on host cytoskeleton, cell plasma membrane lipid rafts and the activation of phosphoinositide 3‐kinase (PI3K). Microscopy studies revealed that K. pneumoniae resides within a vacuolar compartment, the Klebsiella‐containing vacuole (KCV), which traffics within vacuoles associated with the endocytic pathway. In contrast to UV‐killed bacteria, the majority of live bacteria did not co‐localize with markers of the lysosomal compartment. Our data suggest that K. pneumoniae triggers a programmed cell death in macrophages displaying features of apoptosis. Our efforts to identify the mechanism(s) whereby K. pneumoniae prevents the fusion of the lysosomes to the KCV uncovered the central role of the PI3K–Akt–Rab14 axis to control the phagosome maturation. Our data revealed that the capsule is dispensable for Klebsiella intracellular survival if bacteria were not opsonized. Furthermore, the environment found by Klebsiella within the KCV triggered the down‐regulation of the expression of cps. Altogether, this study proves evidence that K. pneumoniae survives killing by macrophages by manipulating phagosome maturation that may contribute to Klebsiella pathogenesis.